Theoretical Evaluation of Eco-friendly Designed Nonionic Sugar-based Surfactants - Rastegar Fatemi, Seyedeh E.; Shafiei, Hadi; Mojtahedi, Mohammad Majid (Letters in Organic Chemistry, 2024)
This study deals with the density functional theory calculations of eco-friendly designed nonionic sugar-based surfactants (SurfRing and SurfLinear). Then, it compares the results with the structural and electronic properties of a fatty alcohol surfactant (SurfFA). All geometry optimizations and energy calculations were performed using M06-2X functional and 6-31G(d,p) basis sets. The quantum chemistry reactivity parameters showed the effect of hydrophilic fragment structure on intramolecular interactions and conformational stability of surfactants. The results showed that SurfRing is more reactive than SurfFA. Based on Bader’s quantum theory of atoms in molecules (QTAIM), one intramolecular hydrogen bond (O43…H67128;•O57, EHB: -11.9 kcal.mol-1) is characterized for SurfRing, while two hydrogen bond interactions (O63…H60128;•O59 and O65…H64128;•O63 with EHB of -13.0, and -12.3 kcal.mol-1, respectively) form between the hydroxyl groups of SurfLinear. These intramolecular hydrogen bonds are partially covalent interactions. Natural bond orbital analysis reveals that the most prominent interaction energy is electron donation from the oxygen atom lone pair to the antibonding orbital of the O128;•H bond supporting the results obtained from the AIM calculations.
Keywords: amphoteric surfactants